Preclinical and clinical assessment of immune checkpoint inhibitor-associated left ventricular dysfunction. (25th November 2020) - Michel, L; Hendgen-Cotta, U.B; Mincu, R.I; Helfrich, I; Korste, S; Mrotzek, S.M; Rischpler, C; Herrmann, K; Ugurel, S; Zimmer, L; Coman, C; Ahrends, R; et al.
Abstract: Background: Immune checkpoint inhibitor (ICI) therapy has improved treatment of advanced cancers but is associated with yet incompletely characterized cardiotoxic side effects. While inflammatory cardiac complications were initially described as a rare phenomenon, emerging evidence indicates frequent cardiotoxicity, particularly latent left ventricular (LV) dysfunction. Distinct clinical characteristics and potential pathomechanisms are so far unknown. Purpose: This study aims to investigate incidence and frequency of LV dysfunction in patients receiving ICI therapy for malignant melanoma. Using a suitable melanoma mouse model, ICI-related cardiotoxicity will be reenacted to identify potential underlying pathomechanisms. Methods: Patients receiving ICI therapy for stage IV melanoma that presented in our cardio-oncology unit were evaluated at baseline and four weeks after initiation of therapy including echocardiography, cardiac biomarkers, and dobutamine stress echocardiography in the absence of contraindications. Patients with decreased LV ejection fraction (LVEF) were further evaluated by 18-fludeoxyglucose PET-MRI to assess manifest myocarditis. To elucidate underlying pathomechanisms, we established a melanoma mouse model that showed profound response to anti-programmed death 1 (PD1) ICI therapy. Immune cell infiltration was assessed by flow cytometry and light sheet fluorescence microscopy. Myocardial biochemical function was analyzed using a multi-omics mass spectrometry-based approach. Results: Seven patients were included to the analysis. Six patients received a combination ICI therapy with ipilimumab and nivolumab, and one patient received nivolumab monotherapy. Echocardiography revealed significantly decreased 3D-LVEF after 4 weeks of therapy in treated patients (p=0.021). A reduced global longitudinal strain was found in six of seven patients. Remarkably, dobutamine stress echocardiography revealed a more pronounced LVEF-decrease (p=0.009) as a sign for impaired myocardial contractility with a mean decrease of 5 percentage points. Using the melanoma mouse model, we were able to recapitulate the disease phenotype as indicated by decreased LVEF and impaired response to inotropic stress during mouse pressure/volume catheterization. Increased concentrations of intramyocardial CD4+ and CD8+ T cells were found in mice treated with anti-PD1 ICI therapy compared to controls (p=0.01). Mass spectrometry revealed disrupted energy metabolism and calcium homeostasis as a putative underlying pathomechanism for impaired myocardial function. Conclusions: ICI-related left ventricular dysfunction may affect a large proportion of patients and potentially increase cardiac morbidity and mortality. Preclinical data proposes myocardial lymphocyte infiltration and disruption of cardiomyocyte metabolism as the underlying pathomechanism. Prospective studies are now needed for a further characterization of this novel form of ICI-related cardiotoxicity. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): IFORES research grant, Medical Faculty, University Duisburg-Essen, Germany